Post-Romantic Experiments: Rethinking Gottfried Keller’s Poetry (KULT_online, 2012)
Despite its impressive thematic and aesthetic range, Gottfried Keller’s lyrical work has long suffered from critical neglect. It is undoubtedly his prose to which Keller owes his reputation as one of the 19th century’s literary luminaries. For generations, high-school students have been treated to his novella, Romeo and Juliet of the Village. Most scholars, meanwhile, typically preoccupy themselves with Keller’s major novel, Green Henry. In his comprehensive study, Die Lyrik Gottfried Kellers (Gottfried Keller’s Poetry), Gert Sautermeister demonstrates how the Swiss author’s poetry may account for his status as a precursor of modernism as well. Further, Sautermeister’s book reminds us that a philologist’s careful attention to form, language, and political contexts will yield more relevant insights into a text than theoretical overload.